2018
DOI: 10.15835/nbha47111074
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancing Effect of Plants Growth Biostimulants in Garlic Cultivation on the Chemical Composition and Level of Bioactive Compounds in the Garlic Leaves, Stems and Bulbs

Abstract: The aim of the study was to evaluate the effect of biostimulants enhancing plant growth and development, i.e. organic stimulator based on metal sulphates, Bacillus subtilis, humic acids, on the chemical composition and level of bioactive compounds in garlic leaves, stems, and bulbs. The study was conducted in three growing seasons on the ‘Ornak’ winter garlic cultivar. The propagating material was treated in solutions of the biostimulants and after emergence the plants were sprayed with the products three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
5
21
0
Order By: Relevance
“…Results obtained from the present investigation were in agreement with findings from previous studies that demonstrated that protein hydrolysates boosted ascorbic acid content and antioxidant activity in fruits of greenhouse pepper [6] and tomato [49,62]. The latter positive effects could be assigned to the activation of the key enzymes involved in cell antioxidant homeostasis, whereas the increase in nutrient assimilation recorded in our trial did not presumably lead to the enhanced synthesis of amino acids such as phenylalanine and tyrosine, which are precursors of polyphenols [66][67][68][69].…”
Section: Antioxidant Compounds and Activitysupporting
confidence: 93%
“…Results obtained from the present investigation were in agreement with findings from previous studies that demonstrated that protein hydrolysates boosted ascorbic acid content and antioxidant activity in fruits of greenhouse pepper [6] and tomato [49,62]. The latter positive effects could be assigned to the activation of the key enzymes involved in cell antioxidant homeostasis, whereas the increase in nutrient assimilation recorded in our trial did not presumably lead to the enhanced synthesis of amino acids such as phenylalanine and tyrosine, which are precursors of polyphenols [66][67][68][69].…”
Section: Antioxidant Compounds and Activitysupporting
confidence: 93%
“…Kulkarni et al [32] reported the positive effect of biostimulant application in increasing spinach content in phenylalanine ammonia lyase, an important enzyme [54] involved in the biosynthesis of phenolic acids. Similarly, Jȩdrszczyk et al [55] recorded a higher antioxidant activity in garlic leaves upon humic acid application. Vasantharaja et al [56] reported a positive biostimulant effect related to the application of 3% Sargassum swartzii extract on phenols and antioxidant activity of Vigna unguiculata .…”
Section: Resultsmentioning
confidence: 91%
“…In their research of the effects of three food‐processing by‐products on tomato fruit metabolic profiles, they found some differences explained by the increase in citric acid content in tomato fruit and the decrease in β‐glucose in treated plants, what indicated the metabolic association related to biostimulant application. Interestingly, garlic leaves had the highest content of fibres, Vitamin C, and polyphenols as well as the highest antioxidant activity of all the organs tested in the research of Jędrszczyk, Kopeć, Bucki, Ambroszczyk, and Skower (2018), whereas the effect of investigated biostimulants depended on the course of weather in different years, and was also organ specific. As reported by Vinković et al (2018), antioxidative activity significantly differed among sweet and hot paprika samples at the same location, mostly depending on differences in capsaicinoids content.…”
Section: Functional Foods Of Plant Origin: the Influence Of Abiotic Smentioning
confidence: 99%